Analysis of Spring's Constantant Value By Combining the Concepts of Hooke's Law and Archimedes' Law - Maida Khoirina; C. Cari; Sukarmin Sukarmin (JIPF (Jurnal Ilmu Pendidikan Fisika), 2018)
The purpose of this study was to determine the constantant value of a spring. This research was an experimental research consisting of several stages of preparation, determining independent and dependent variables, conducting experiments, analyzing and concluding. This research used a simple material that was solid beam with a length of 3.5 cm, width of 3.5 cm, height 4.5 cm and mass of 300 g, two types liquid of water and cooking oil, one spring to be calculated the value of spring constantant. The results showed that the volume of dyed objects was inversely proportional to the increase of the length of the spring and the density of the liquid type affected the magnitude of increase in the length of the spring. The constantant value of the spring in water was 21.43 N/m and the spring constantant value of cooking oil was 21,27 N/m. These results can be used as a proof of the truth of equations that combine the concepts of Hooke's law and Archimedes' Law. It can then be used as an alternative to investigating the value of spring constantant k in addition to Hooke's law experiments and simple harmonic motion.